2014
DOI: 10.12659/msm.889847
|View full text |Cite
|
Sign up to set email alerts
|

Distal pancreatectomy with en bloc celiac axis resection for pancreatic body-tail cancer: Is it justified?

Abstract: BackgroundThe aim of this study was to evaluate the safety and efficacy of distal pancreatectomy with en bloc celiac axis resection (DP-CAR) for pancreatic body-tail cancer.Material/MethodsThe medical records of 12 patients who underwent DP-CAR for pancreatic body-tail cancer were retrospectively studied, together with a literature review of studies including at least 3 cases of DP-CAR.ResultsThere were no deaths among our 12 cases. Postoperative morbidity developed in 9 cases and was successfully managed by n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Seven studies 4,9,13,27,28,30,31 including 114 patients undergoing DP-CAR reported intraoperative blood loss. The mean blood loss varied from702 mL to 1867.5 mL.…”
Section: Intraoperative Outcomesmentioning
confidence: 99%
“…Seven studies 4,9,13,27,28,30,31 including 114 patients undergoing DP-CAR reported intraoperative blood loss. The mean blood loss varied from702 mL to 1867.5 mL.…”
Section: Intraoperative Outcomesmentioning
confidence: 99%
“…Consistent with these results, Sonohara et al demonstrated that PCa patients with AR had marginally higher recurrence-free survival and longer overall survival without a significant increase in the incidence of severe postoperative complications [33]. Current studies evaluating celiac artery resection also showed that these procedures can be performed safely and with an encouraging median survival [32,34]. Further analyses suggested the improvement to be a consequence of newly developed and more effective chemotherapeutical regimens used in neoadjuvant settings.…”
Section: Radical Resection In Pca: "The Holy Grail"mentioning
confidence: 81%
“…In the first meta-analysis evaluating AR in patients undergoing pancreatectomy for PCa, AR was discouraged as standard of care and was associated with remarkably higher perioperative morbidity (OR = 2.17) and mortality (OR = 5.04) and poor survival (OR = 0.50) [4]. Conversely, in a recent study, Del Chiaro et al demonstrated the feasibility and safety of AR in pancreatectomy, which was accompanied by increased survival compared with palliative procedures and showed no difference in postoperative mortality and morbidity, even though it was associated with longer operation time and higher blood loss [31,32]. Consistent with these results, Sonohara et al demonstrated that PCa patients with AR had marginally higher recurrence-free survival and longer overall survival without a significant increase in the incidence of severe postoperative complications [33].…”
Section: Radical Resection In Pca: "The Holy Grail"mentioning
confidence: 99%
“…In the literature, liver ischemic complications vary a lot: 0–62% [ 1 , 2 , 4 , 7 , 11 , 17 , 18 ], but seem to be around 20% in the larger studies [ 1 , 4 , 7 ]. Ischemic gastropathy is also not infrequent, ranging from nil [ 11 , 18 ] to 29% [ 9 ], but generally occurs in around 10% of patients [ 1 , 2 , 12 , 17 ]. Few authors emphasize the need for preservation, or reconstruction of the left gastric artery [ [17] , [18] , [19] ], whereas most others have not found the need for it.…”
Section: Discussionmentioning
confidence: 99%
“…DP-CAR is generally associated with significant mortality and morbidity, much higher than “straightforward” pancreatoduodenectomy, or DP, even in experienced hands. Mortality is reported around 10% [ 1 , 2 , 4 , 5 ] and varies between 3.5% and 18% [ 3 , [6] , [7] , [8] , [9] ], although nil mortality has also been documented [ [10] , [11] , [12] ]. Median survival after DP-CAR is generally less than 20 months [ 1 , 2 , 4 , 6 ], but this may reflect older experience before neoadjuvant chemotherapy (NAC) was the rule for locally advanced PC.…”
Section: Introductionmentioning
confidence: 99%